Associations of ADL Disability With Trunk Muscle Mass and Muscle Quality Indicators Measured by Opportunistic Chest Computed Tomography Imaging Among Older Inpatients - Jing, Xiaofan; Tan, Lingling; Fu, Hongbo; Yang, Ling; Yang, Ming (Frontiers in Medicine, 2021)
Objectives: Sarcopenia is an important predictor of dependence in activities of daily living (ADL disability); however, the association between muscle quality and ADL disability has not been established. We aimed (1) to assess the feasibility of measuring trunk muscle mass and muscle quality by chest CT images; and (2) to explore the possible associations of ADL disability with these muscle mass and muscle quality indicators among older inpatients. Methods: We included older patients in an acute care ward. ADL disability was defined as the Barthel Index (BI) score ≤ 60 points. Unenhanced chest CT images at the 12th thorax (T12) vertebral level were used to segment skeletal muscle area (SMA) and intermuscular adipose tissue (IMAT) and to measure the mean skeletal muscle radiodensity (SMD). Skeletal muscle index (SMI), the muscle mass indicator, was calculated by SMA (cm2) / body height squared (m2). The percentage of IMAT (IMAT%) was calculated using the equation: IMAT% = IMAT/ (SMA+ IMAT) × 100%. SMD, IMAT, and IMAT% were the muscle quality indicators. Kendall’s tau rank correlation coefficients (τ) were calculated to explore the correlations. Univariate and multivariate logistic regression models were performed to calculate odds ratios (OR) and 95% confidence interval (CI). Results: We included 212 participants. SMI and SMD were positively and significantly associated with the BI score (τ=0.14 and 0.31, respectively, both P<0.001); whereas IMAT and IMAT% were negatively and significantly associated with the BI score (τ= -0.21, P<0.001; τ= -0.21, P<0.012). After adjusting for confounders, SMI (adjusted OR 1.03, 95% CI 0.97-1.09) was not independently associated with ADL disability; however, SMD (adjusted OR 0.94, 95% CI 0.88-0.99), IMAT (adjusted OR 1.11, 95% CI 1.03-1.20), and IMAT% (adjusted OR 1.09, 95% CI 1.02-1.16) were independently associated with ADL disability. Subgroup analysis found similar results in men; however, none of these indicators were independently associated with ADL disability in women. Conclusion: Trunk muscle quality indicators (SMD, IMAT, and IMAT%) measured by chest CT images, but not SMI, are independently associated with ADL disability in a single-center study population of older inpatients, especially in men. Further research is necessary to validate our findings.